Westonci.ca offers quick and accurate answers to your questions. Join our community and get the insights you need today. Explore thousands of questions and answers from knowledgeable experts in various fields on our Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

how to solve this equation showing step by step. 3(t - 1) = 9 + t

Sagot :

1st: Expand the bracket
3t-3=9+t
2nd: Add the 3 to get rid of it on the first side. Do this to both sides
3t=12+t
3rd: Take away the t on the left hand side and one on the right hand side to just be left with t's on one side and integers on the other side
2t=12
4th: Divide both sides by 2 to find 1t
t=6

Hope this helps!! :)

3(t-1)=9+t
3t-3=9+t
3t-t=3+9
2t=12 (divide both sides by 2)
t=6
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.